Readability and adaptation of children’s literature: an interpersonal metaphor perspective - Liu Yan (Journal of World Languages)
Readability receives attention from people with different theoretical bases. Starting from a new perspective of interpersonal metaphor, this paper aims to deal with the readability and adaptation of children’s literary work. Adopting a qualitative method, this paper selects a small portion of the data from a larger data set for illustration, in the hope of approaching the two aspects: (1) the manners of realization in the adaptation of the parts concerning mood and modality metaphor in the data; (2) the strategies of the adjustment of interpersonal metaphor-related parts in the data, and the effect of these strategies on readability. The research findings are: (1) two manners of realizations have been found regarding adjustment and readability involving either mood or modality metaphor; (2) three strategies are evidenced to be entailed: unpacking, demetaphorization, and maintenance, where the first two reduce readability, and the last one contributes to the same readability. Thanks to the consistency in the exploitation of the theoretical basis, the study offers fresh insights into readability studies.